OBJECT RELATIONS THEORIES AND PSYCHOPATHOLOGY a comprehensive text. - Summers, Frank ([S.l.] : ROUTLEDGE, 2023)
Twenty-nine years since the first edition was released, Frank Summers has renewed his lucid and thorough clarification of the various object relations theories to demonstrate their evolution and continued significance for therapeutic practice. This volume includes elucidation of the major scholarship that has advanced the ideas of object relations theorists such as Fairbairn, Klein, Winnicott, Kernberg, and Kohut, since the publication of the first edition. A thorough and detailed new chapter devoted to the emergence and development of relational psychoanalysis has been added to make this volume a state of the art articulation of current object relations thinking. The ideas and assumptions of each theory relative to metapsychology, psychopathology, and treatment are expounded, alongside a critical evaluation of the strengths and limitations of each approach. With extensive use of historic case material, Summers shows how each object relations theory yields specific clinical approaches to a variety of syndromes, and how these approaches entail specific modifications in clinical technique. This volume will be essential reading for all analysts, psychologists, psychiatrists, and social workers who wish to familiarize themselves with object relations theories in general, sharpen their understanding of the work of specific object relations theorists, or enhance their ability to employ these theories in their clinical work.
Keywords: Object relations (Psychoanalysis); PSYCHOLOGY / Psychopathology / General; PSYCHOLOGY / Psychotherapy / General; PSYCHOLOGY / Mental Health